(untitled) (International journal of artificial intelligence, 2025)
Genetik engineering and biotechnology represent transformative forces in modern medicine, reshaping diagnostics, therapeutics, and preventive care. This article explores key advancements, including CRISPR-Cas9 genome editing, gene therapy for inherited disorders, and the biotechnological development of mRNA vaccines. It also examines the integration of personalized medicine, stem cell technologies, and molecular biology in clinical practice. While these innovations hold immense promise, they also raise significant ethical, legal, and social concerns. The article highlights both the opportunities and challenges of genetic engineering in healthcare and concludes with a perspective on future directions in this rapidly evolving field.